1997
DOI: 10.1007/bf01294719
|View full text |Cite
|
Sign up to set email alerts
|

Gammahydroxybutyrate (GHB) receptor ligand effects on evoked synaptic field potentials in CA1 of the rat hippocampal slice

Abstract: GHB produced a concentration-dependent depression of evoked synaptic field potentials (EFPs) recorded extracellularly in the CA1 region of the in vitro rat hippocampal slice. The concentration/response function revealed a threshold near 1 mM, with IC50 of 10.85 mM and a Hill coefficient of 1.29. The gamma-aminobutyric acid B-receptor (GABA-B) agonist baclofen also depressed the EFP, but even maximally effective concentrations of the GABA-B antagonist 2-hydroxy-saclofen (800 microM) could not completely block t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…Live, acute hippocampal slices were prepared by procedures used routinely to produce slices that can remain electrophysiologically active for up to 12 hr after preparation (King et al, 1997; Thinschmidt et al, 2003). Rats were euthanized by rapid decapitation under general anesthesia induced with an intraperitoneal injection (0.875 ml/kg of 5:9 mixture of 20 mg/ml xylazine:100 mg/ml ketamine).…”
Section: Methodsmentioning
confidence: 99%
“…Live, acute hippocampal slices were prepared by procedures used routinely to produce slices that can remain electrophysiologically active for up to 12 hr after preparation (King et al, 1997; Thinschmidt et al, 2003). Rats were euthanized by rapid decapitation under general anesthesia induced with an intraperitoneal injection (0.875 ml/kg of 5:9 mixture of 20 mg/ml xylazine:100 mg/ml ketamine).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, King et al (46) revealed that GHB dose-dependently depresses the field potential (FP) in vitro. This action of GHB was depressed by a large concentration of 2-OH-saclofen, but not by NCS-382 at concentrations up to 5 mM.…”
Section: In Vivo and In Vitro Effects Of Ncs-382mentioning
confidence: 98%
“…Accordingly, Xie and Smart (74) showed a hyperpolarization and a small membrane conductance increase when GHB was applied to hippocampal CA1 pyramidal neurons; this effect being completely abolished by the GABA B antagonist, CGP 35348. Moreover, King et al (46) revealed that GHB dose-dependently depresses the field potential (FP) in vitro. This action of GHB was depressed by a large concentration of 2-OH-saclofen, but not by NCS-382 at concentrations up to 5 mM.…”
Section: In Vivo and In Vitro Effects Of Ncs-382mentioning
confidence: 99%
“…This depression was obtained at higher concentrations (10 mM) than those of the present study and it was reversibly blocked by a selective GABA B antagonist. Thus, GHB can also activate presynaptic GABA B receptors to reduce inhibitory and excitatory transmitter release as described in other reports (Xie and Smart, 1992a, b;King et al, 1997). In the presence of TTX (1 mM), no reduction in mIPSCs amplitude and frequency was observed indicating that the depressing effect of GHB on sIPSCs was not due to a reduced postsynaptic sensitivity to GABA but to a presynaptic depression of GABA release.…”
Section: Discussionmentioning
confidence: 71%
“…Spontaneous synaptic currents were recorded from SNc dopaminergic neurons in the presence of the GABA B antagonist CGP 55845A (1 mM) to prevent the effects of GHB on the GABA B receptor (Xie and Smart, 1992a, b;King et al, 1997). This spontaneous activity appeared as rapidly rising inward currents at a frequency of 8.91 7 0.75 Hz and an amplitude of 28.1 7 2.4 pA (n ¼ 8).…”
Section: Effects Of Ghb On Sipscsmentioning
confidence: 99%